Nutrition, lifestyle, and cognitive performance in esport athletes - Goulart, Jenna B.; Aitken, Logan S.; Siddiqui, Saman; Cuevas, Marisa; Cardenas, Jacqueline; Beathard, Karen M.; Riechman, Steven E. (Frontiers in Nutrition, 2023)
Electronic sports, termed esports, is a growing athletic activity in which high levels of attention and cognitive performance are required. With its increasing popularity and competitiveness, interest in strategies to improve performance have emerged. Improving esports athlete performance, namely cognitive endurance, and resilience, may lie in nutritional or lifestyle factors. The Nutrition, Vision, and Cognition in Sport Studies (IONSport) investigated nutritional and behavioral factors that can influence cognition via 3- dimensional multiple objects tracking test (3DMOT) via Neurotracker X (NTx) software. The purpose of this study was to characterize the lifestyle of high level esports athletes with detailed nutrition, sleep, and physical activity assessments, and their association to gaming related cognitive performance. 103 male and 16 elite female esports athletes aged 16 to 35 years old completed surveys, food records, and cognitive testing sessions sessions over 10 days. Participants were instructed to maintain their normal dietary and lifestyle habits. There were positive significant associations between average NTx scores and the following nutrients: magnesium, phosphorous, potassium, sodium, zinc, selenium, thiamin, niacin, vitamins B6 and B12, folate, cholesterol, saturated, polyunsaturated, and monounsaturated fats, omega-6 and omega-3 fatty acids, and choline. Majority of participants did not meet recommended dietary allowances (RDAs) for these micronutrients nor the recommended intakes for dairy, fruit, and vegetables. There was a significant (p=0.003) positive (r= 0.272) association between total vegetable intake and average NTx score. There was a significant negative association (p=0.015) with our final sustain session, which measured cognitive resilience, and the Stanford Sleepiness Scale score. Repeated measures analysis was done with these groups over the 18 core NTx sessions. There were significant (p=0.018) differences between the two groups with those who consumed the recommended amount of protein or more performing significantly better on NTx over the 18 sessions than those that did not consume enough protein. Those who consumed the recommended intakes for riboflavin, phosphorous, vitamin B12, and selenium performed significantly better over the 18 core NTx sessions than those that did not meet the recommended amounts. The need for a nutrition intervention that is rich in protein, vitamins, and minerals is warranted in this population.